2017
DOI: 10.1002/jez.b.22738
|View full text |Cite
|
Sign up to set email alerts
|

Spotted Gar and the Evolution of Innate Immune Receptors

Abstract: The resolution of the gar genome affords an opportunity to examine the diversification and functional specialization of immune effector molecules at a distant and potentially informative point in phylogenetic development. Although innate immunity is effected by a particularly large number of different families of molecules, the focus here is to provide detailed characterization of several families of innate receptors that are encoded in large multigene families, for which orthologous forms can be identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 98 publications
4
26
0
Order By: Relevance
“…Our previous analyses of spotted gar immune genes revealed shared characteristics with those of both teleosts and tetrapods, but left important aspects of the ray-nned sh immunogenome unresolved 7,44 . For a comprehensive understanding of holostean immune genes, we surveyed the bow n genome and a newly generated bow n immune tissue transcriptome (Supplementary Note 4).…”
Section: Unraveling the Holostean Immunogenomementioning
confidence: 96%
See 1 more Smart Citation
“…Our previous analyses of spotted gar immune genes revealed shared characteristics with those of both teleosts and tetrapods, but left important aspects of the ray-nned sh immunogenome unresolved 7,44 . For a comprehensive understanding of holostean immune genes, we surveyed the bow n genome and a newly generated bow n immune tissue transcriptome (Supplementary Note 4).…”
Section: Unraveling the Holostean Immunogenomementioning
confidence: 96%
“…Toll-like Receptors (TLRs) provide initial immune responses to infection in animals 60 . Bow n possesses 20 TLR genes from all six families, twice the number of human TLRs 61 , more than the 16 functional spotted gar TLRs 7,44 , and almost on par with the more than 20 teleost TLR genes 62,63 ( Supplementary Fig. 10, Supplementary Table 12, Supplementary Note 4).…”
Section: Unraveling the Holostean Immunogenomementioning
confidence: 99%
“…AMCP sequences) for NITR sequences, we employed spotted gar NITR I domains (Wcisel et al 2017) as queries for BLASTP searches (e value cutoff < 1e-15) as the high rate of sequence evolution in NITR V domains limits their utility for effective homology searches over deep evolutionary time scales. In order to identify bowfin NITR transcripts, we used the candidate NITR sequences encoded by the genes described above and all reported spotted gar NITR I domains (Wcisel et al 2017) as queries for tBLASTn searches (e values <1e-10) against immune tissue RNA-seq from bowfin 0039 (Thompson et al 2021) and from bowfin available from PhyloFish (Pasquier et al 2016) ( Supplementary Note 1 ). Resultant protein sequences were manually inspected and those lacking an Ig domain or found to encode Ig light chain proteins were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Wcisel, Ota, Litman, and Yoder () investigated the gar immune gene repertoire and found that although the gar innate immune receptors share more sequence similarities with teleost sequences, their genomic organization often resembles that possessed by tetrapod genomes.…”
mentioning
confidence: 99%
“…Kawasaki et al (2017) expanded their investigations of the evolution of the SCPP protein family involved in the formation of mineralized tissues such as bone, dentine, enamel, and ganoin, finding that the SCPP family is larger in gar than any other vertebrate studied thus far. Wcisel, Ota, Litman, and Yoder (2017) investigated the gar immune gene repertoire and found that although the gar innate immune receptors share more sequence similarities with teleost sequences, their genomic organization often resembles that possessed by tetrapod genomes. Beaudry et al (2017) used the spotted gar genome as starting point to illuminate the evolutionary history of non-visual opsin genes among vertebrates.…”
mentioning
confidence: 99%